(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article provides a historical overview of the construction of the concept of Constitution, including differentiating States of Law and Police States. It then presents a more current view of the Philosophy of Law, notably exposing neoconstitutionalist or, as it prefers to call it, post-positivist ideas, especially related to human rights. At the end, it proposes a reflection on the profound legal transformation represented by the rebalancing between the sources of law, with the increased relevance of jurisprudence, even in the face of the reduction of the legislator’s performance in the alteration of legal norms, in a phenomenon that requires the interpreter and the applicator of the Law to pay extra attention, so that any departure from legal certainty in favor of a more flexible system does not generate effects opposite to those desired by its actors.